IMPLEMENTATION OF MICROSOFT ACCESS AS AN EFFECTIVE SOLUTION FOR FINANCIAL REPORTING IN GROCERY STORE SMEs - Wijaya, Ahmad Robi; Yuniarti, Evi; Mareta, Fitri (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
Small and Medium Enterprises (SMEs) play a strategic role in the Indonesian economy, yet many SMEs still face challenges in financial recording due to manual bookkeeping practices. This study aims to design, implement, and evaluate an accounting information system based on Microsoft Access to improve the efficiency, effectiveness, and accuracy of financial reporting at FMG Grocery Store SME. The research employs a descriptive qualitative approach using primary data obtained through interviews, observations, and documentation. System development follows the System Development Life Cycle (SDLC) method, including planning, design, development, testing, and implementation. The results indicate that the Microsoft Access-based system accelerates transaction recording, reduces human error, and automatically generates financial statements such as journals, ledgers, income statements, balance sheets, equity reports, and cash flow statements. The system also supports business decision-making by providing structured and real-time financial information. The findings suggest that Microsoft Access can serve as a practical, low-cost, and user-friendly solution for SME financial management and digital transformation.